2015
DOI: 10.1002/jhm.2481
|View full text |Cite
|
Sign up to set email alerts
|

A taxonomy of seven‐day readmissions to an urban teaching hospital

Abstract: BACKGROUND Understanding the mechanism of unplanned hospital readmissions is necessary for accurate prediction and prevention. OBJECTIVE To identify specific mechanisms of unplanned readmissions through medical narratives obtained from chart reviews. DESIGN Retrospective chart review. SETTING Urban tertiary care hospital. PATIENTS Two hundred seventy patients accounted for 335 unplanned 7‐day readmissions between July 2010 and July 2011. MEASUREMENTS Readmissions were classified into 1 of 5 distinct categories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Additional file 6 provides more information on the interviews with care providers and/or patients. In 7 studies the patient was approached [2123, 25, 3032] and in 5 studies the patient or caregiver was approached [14, 2629]. In 4 studies it was mentioned that the results of the interview were available for the reviewers during their assessment of preventability, however, it was not specified if and how these results influenced the preventability assessment [14, 22, 26, 29].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Additional file 6 provides more information on the interviews with care providers and/or patients. In 7 studies the patient was approached [2123, 25, 3032] and in 5 studies the patient or caregiver was approached [14, 2629]. In 4 studies it was mentioned that the results of the interview were available for the reviewers during their assessment of preventability, however, it was not specified if and how these results influenced the preventability assessment [14, 22, 26, 29].…”
Section: Resultsmentioning
confidence: 99%
“…The other 5 studies did not specify whether or not the additional patient/caregiver information was used to assess the preventability [25, 28, 3032]. In the study of Burke et al [23], only 6 patients were interviewed during a pilot phase. After the pilot, they concluded that the interviews did not provide additional data to the patient’s medical record.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations